2004
DOI: 10.1111/j.1365-2036.2004.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

An enema formulation of alicaforsen, an antisense inhibitor of intercellular adhesion molecule‐1, in the treatment of chronic, unremitting pouchitis

Abstract: SUMMARYBackground: Pouchitis is the major long-term complication of ileal pouch-anal anastomosis for ulcerative colitis. The incidence of pouchitis is as high as 50% several years after surgery. Two-thirds of pouchitis patients suffer recurrence. Of those who recur, onequarter suffer from chronic, unremitting pouchitis. Current treatments for this disorder are disappointing. Aim: To determine whether a topically administered enema formulation of ISIS 2302 (alicaforsen), an antisense inhibitor of intercellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 8 publications
(13 reference statements)
1
78
0
4
Order By: Relevance
“…A randomized trial of ciprofloxacin and metronidazole showed that patients treated with ciprofloxacin experience significantly greater reductions in the PDAI scores and fewer adverse effects than those treated with metronidazole [67] . Other agents have been reported in open-labeled trials including tetracycline, clarithromycin, amoxicillin/clavulanic acid, doxycycline, rifaximin, and budesonide enemas [68] , alicaforsen enemas, an anti-sense inhibitor of intercellular adhesion molecule-1 [69] , and AST-120, a highly adsorptive, porous, carbon microspheres [70] .…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized trial of ciprofloxacin and metronidazole showed that patients treated with ciprofloxacin experience significantly greater reductions in the PDAI scores and fewer adverse effects than those treated with metronidazole [67] . Other agents have been reported in open-labeled trials including tetracycline, clarithromycin, amoxicillin/clavulanic acid, doxycycline, rifaximin, and budesonide enemas [68] , alicaforsen enemas, an anti-sense inhibitor of intercellular adhesion molecule-1 [69] , and AST-120, a highly adsorptive, porous, carbon microspheres [70] .…”
Section: Treatmentmentioning
confidence: 99%
“…Alicaforsen (ISIS 2302) administered in enema form may be useful in the management of left UC and antibiotic-resistant chronic pouchitis (95,96). A double-blind, placebo-controlled phase-2 study was recently reported where 120 patients with left active UC received alicafors-en enemas at various doses.…”
Section: Anti-leukocyte Adhesion Therapiesmentioning
confidence: 99%
“…To our knowledge, this is the only case series investigating the role and potential efficacy of the ICAM-1 antisense oligonucleotide alicaforsen in chronic refractory pouchitis in UC patients after proctocolectomy, besides one open-label study with 12 patients. 13 …”
Section: Introductionmentioning
confidence: 99%